Merkel cell polyomavirus IgG antibody levels are associated with progression to AIDS among HIV-infected individuals - Vahabpour, Rouhollah; Nasimi, Maryam; Naderi, Niloofar; Salehi-Vaziri, Mostafa; Mohajel, Nasir; Sadeghi, Farzin; Keyvani, Hossein; Monavari, Seyed Hamidreza (Archives of virology, 2017)
The association of Merkel cell polyomavirus (MCP y V) with Merkel cell carcinoma (MCC) in immunocompromised individuals has been revealed in a number of surveys. The study of MCP y V specific antibody titers and viral loads in such patients has a great attraction for research groups interested in viral reactivation. In this cross-sectional study to evaluate MCP y V antibody titer, DNA prevalence and viral load in peripheral blood mononuclear cells (PBMCs), we examined 205 HIV-1 infected patients and 100 un-infected controls. The HIV-1 infected patients divided into two groups (HIV/AIDS and non-AIDS) according to their CD4 status. Total IgG antibody titer against MCP y V was analyzed by virus like particle (VLP)-based enzyme linked immunosorbent assay (ELISA). Presence of MCP y V-DNA in subject’s PBMCs was examined by quantitative real-time PCR assay. Levels of anti-MCP y V IgG in HIV/AIDS patients were significantly higher than those in non-AIDS HIV-infected and control subjects ( p value